AN ANALYSIS OF APPLIED SUBTITLING STRATEGIES IN THE SUBTITLES OF THE FILM "THE INTERPRETER" - Indra Agustian, - (2008)
Translation is achallenging job for the translators at Resent since the science and technology provide many new forms of translation Work which is rapidly developed. One ofthem is translation offilms for aforeign language audience. To handle the translation for the films, there is an Audiovisual translation (AVT) as a media covering subtitling and dubbing. However, the ^ubtitlers usually encounter so many problems in the process of subtitling. Realizing that the problems potentially occur in the process, subtitling strategies are really needed to give some directions in solving the problems. Considering that issue, the study entitled An Analysis of Applied Subtitling Strategies in the Subtitles of the Film "The Interpreter" is aimed to find out the strategies of subtitling mostly employed by the subtitler in producing the subtitles and the problems occurred in the process. This study is a descriptive qualitative method. This method has been adopted to produce a systematic and factual description about the gained data. Meanwhile, the data were gathered by using the document analysis technique. The result of this study shows that several subtitling strategies are applied in translating the selected units of translation of the original version: expansion, paraphrase, transfer, imitation, condensation, decimation, deletion and transcription strategy. Furthermore, from the eight subtitling strategies, there are differences ofthe application quantity ofeach strategy. The findings of the research are finally concluded that subtitling strategy mostly adopted in the movie ofThe Interpreter is transfer.